2004
DOI: 10.1023/b:caim.0000041937.63446.f8
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Administration of Trimetazidine Modified Myocardial Perfusion and Left Ventricular Function in 31 Patients with Ischaemic Ventricular Dysfunction

Abstract: In comparison with placebo, the addition of TMZ to myocardial Tc-99m tetrofosmin SPECT improved myocardial perfusion and LVEF, reducing LVESV. These effects were lost in patients with more severe ventricular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…In some other studies, the addition of Trimetazidine to myocardial Tc-99 m sestamibi or tetrofosmin SPECT improved myocardial perfusion and LV function [4547]. …”
Section: Recent Trends In Viability Assessmentmentioning
confidence: 99%
“…In some other studies, the addition of Trimetazidine to myocardial Tc-99 m sestamibi or tetrofosmin SPECT improved myocardial perfusion and LV function [4547]. …”
Section: Recent Trends In Viability Assessmentmentioning
confidence: 99%
“…They found that wall motion dysfunction improved and EF increased. Feola et al [45] studied the effect of 3-day TMZ treatment in patients with ischemic HF. Compared with placebo, TMZ improved EF and reduced LV end-systolic volume.…”
Section: Acute Metabolic Modulationmentioning
confidence: 99%
“…Feola et al studied the changes in myocardial perfusion and global left ventricular function induced by short-term treatment with trimetazidine in patients with ischaemic ventricular dysfunction [118]. They demonstrated a significant improvement in myocardial perfusion during treatment as compared with the images obtained under placebo, and this improvement was accompanied by a significant reduction in left ventricular end-systolic volume and a significant increase in the ejection fraction; however, in the subgroup of patients with the most severe left ventricular dysfunction, the perfusion recovery was not associated with a significant functional improvement [118]. Thus, the functional effect of treatment could be analysed taking into account also the interaction between drug action and perfusion pattern.…”
Section: Gated Spect For the Evaluation Of Left Ventricular Volumes Amentioning
confidence: 99%